Counteracting neuronal nitric oxide synthase proteasomal degradation improves glucose transport in insulin-resistant skeletal muscle from Zucker fa/fa rats - Mezghenna, Karima; Leroy, Jérémy; Azay-Milhau, Jacqueline; Tousch, Didier; Castex, Françoise; Gervais, Sylvain; Delgado-Betancourt, Viviana; Gross, René; Lajoix, Anne-Dominique (Diabetologia, 2014)
Aims/hypothesis Insulin-mediated glucose transport and utilisation are decreased in skeletal muscle from type 2 diabetic and glucose-intolerant individuals because of alterations in insulin receptor signalling, GLUT4 translocation to the plasma membrane and microvascular blood flow. Catalytic activity of the muscle-specific isoform of neuronal nitric oxide synthase (nNOS) also participates in the regulation of glucose transport and appears to be decreased in a relevant animal model of drastic insulin resistance, the obese Zucker fa/fa rat. Our objective was to determine the molecular mechanisms involved in this defect. Methods Isolated rat muscles and primary cultures of myocytes were used for western blot analysis of protein expression, immunohistochemistry, glucose uptake measurements and GLUT4 translocation assays. Results nNOS expression was reduced in skeletal muscle from fa/fa rats. This was caused by increased ubiquitination of the enzyme and subsequent degradation by the ubiquitin proteasome pathway. The degradation occurred through a greater interaction of nNOS with the chaperone heat-shock protein 70 and the co-chaperone, carboxyl terminus of Hsc70-interacting protein (CHIP). In addition, an alteration in nNOS sarcolemmal localisation was observed. We confirmed the implication of nNOS breakdown in defective insulin-induced glucose transport by demonstrating that blockade of proteasomal degradation or overexpression of nNOS improved basal and/or insulin-stimulated glucose uptake and GLUT4 translocation in primary cultures of insulin-resistant myocytes. Conclusions/interpretation Recovery of nNOS in insulin-resistant muscles should be considered a potential new approach to address insulin resistance.